Simple Bookkeeping Training for Micro Businesses in Banten Province - Ayu Noorida Soerono; Intan Puspanita; Edwin Perdana Adiwijaya (EQUATOR SINAR AKADEMIA, 2023)
The background for this community service activity is the information that most micro-entrepreneurs in Banten do not know how to keep financial records/bookkeeping of their business. Based on this, training activities and bookkeeping assistance were carried out for micro businesses in Banten, especially in Serang Regency, Serang City, and South Tangerang City. The training was given to 20 micro-entrepreneurs in the Regency/City, with the stages of providing material on simple bookkeeping, as well as providing assistance for the preparation of the bookkeeping. The result of this activity is that the micro business community feels helped and can prepare simple financial reports.